CASES OF DIFFUSE LARGE B-CELL LYMPHOMA WITH FUNCTIONAL INTRON MUTATIONS IN THE TP53 GENE - E. N. Voropaeva; M. I. Voevoda; T. I. Pospelova; V. N. Maksimov (Сибирский онкологический журнал)
Background. the presence of functionally significant intron mutations in the TP53 gene was demonstrated in experiments in vitro and on samples of patients with some variants of non-Hodgkin’s lymphomas. to date, the studies of TP53 in tumor tissue of patients with diffuse large B-cell lymphoma (dlBCl) have been focused on the mutations in 5–8 exons of the gene. For these reasons, further studies of the spectrum of changes in the intron sequences of the TP53 gene and the determination of their functional effect in dlBCl are required.Description. We present two case reports that are of interest as the cases for detection of functionally significant intron TP53 mutations in dlBCl tissue, first published in the Russian scientific literature. the first clinical case of dlBCl was clinically characterized by extranodal tumor at the onset of the disease, severe symptoms of tumor intoxication, high paraclinical tumor activity, and early hemoblastosis recurrence. the second case of dlBCl was characterized by initially massive tumor lesion, rapidly progressive course of the disease, severe symptoms of tumor intoxication, high paraclinical tumor activity and poor response to therapy with subsequent generalization of lymphoma. Conclusion. Mutations in the TP53 gene are the driver of the tumor process, serve not only as a marker of aggressive tumor progression, but also as an independent predictor of reduced sensitivity to treatment. the presented clinical cases show that an in-depth analysis of the results of the TP53 sequencing in tumors and functional assessment of all detected changes, including changes in the introns of the gene and involving in silico analysis techniques, are necessary.